Clues for renewing anti-racist social action: https://doi.org/10.53809/TS_ISS_2022_n.2_7-30 ("Temas Sociais" Journal, 2022)
Anti-racist social action is not proving effective at combating contemporary racism. Traditional awareness models suffer from serious limitations that prevent them from achieving their stated objectives. In this paper, these limits are described and explained, based on an analysis of the dominant models implicit in current anti-racist interventio0n.Second, two new conceptual tools are proposed that are essential to reframe anti-racist action, so that socio-educational intervention is truly able to transform and eliminate moral boundaries. Finally, several operational proposals are presented and described to renew anti-racist social action from a critical-transformative perspective: critical reflexivity, the decolonization of one’s own culture, understanding to transform, the enabling of racialized and discriminated groups, participatory communication, and communicational empowerment.
Keywords: Racism, Implicit Model, Moral Boundaries, Participatory Communication, Communicational Empowerment, Critical Reflexivity, Functional Interculturality, Anti Oppressive Practice.